Contemporary clinical psychology - Plante, Thomas G. (Hoboken, N.J. : John Wiley & Sons, 2011)
'Contemporary Clinical Psychology, Third Edition introduces students to this fascinating profession from an integrative, biopsychosocial perspective. Thoroughly updated to include the latest information on topics central to the field, this innovative approach to studying clinical psychology delivers an engaging overview of the roles and responsibilities of today's clinical psychologists that is designed to inform and spark interest in a future career in this dynamic field. Highlighting evidence-based therapies, multiple case studies round out the portrayal of clinical practice. Designed for graduate and undergraduate students in introductory clinical psychology courses'--Provided by publisher
What is contemporary clinical psychology?. Foundations and early history of clinical psychology -- Recent history of clinical psychology -- Research : design and outcome -- The major theoretical models : psychodynamic, cognitive-behavioral, humanistic, and family systems -- Integrative and biopsychosocial approaches in contemporary clinical psychology -- Contemporary psychological assessment I : interviewing and observing behavior -- Roles and resonsibilities -- Contemporary psychological assessment II : cognitive and personality assessment -- Psychotherapeutic interventions -- Psychotherapeutic issues -- Areas of specialization -- Consultative, teaching, and administrative roles -- Ethical standards -- Current and future trends and challenges -- Becoming a clinical psychologist : a road map
Keywords: Psychology, Clinical; Mental disorders -- Therapy; Psychotherapy